Making small sports clubs manageable and economically sustainable – a study on clay target shooting in Italy. Issue 5 (2nd September 2016) - Musso, Fabio; Richelieu, André; Francioni, Barbara
Abstract : This paper examines the case of clay shooting clubs in Italy by focusing on their main characteristics. An analysis has been conducted on a sample of 200 clay target shooting clubs. Results show that most clubs only offer shooting practice, being rather insensitive to the usability, comfort and aesthetics of the environment in which shooting sessions are performed. Confirming the above, findings from the cluster analysis revealed that the most effective clubs are those with a larger size, good organization and management, they have the ability to attract shooters, while providing a wide range of services that contribute to additional revenues and financial viability. This research adds to the sports management literature in two main ways. First, it conducts an in-depth analysis of the management of non-profit sports clubs. Second, it brings to the fore two options in how better management approaches could be developed.